ANALISIS KETEPATAN KODE DIAGNOSIS DAN KESESUAIAN DIAGNOSIS PASIEN RAWAT INAP PADA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DENGAN BERKAS REKAM MEDIS DI RUMAH SAKIT PERTAMINA CIREBON - , TRIA DISRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Background of Problem : The encoding of patient diagnosis in Pertamina Hospital - Cirebon has been using a computerized system. It means that for entry data of disease diagnosis and hospitalized patient codes the medical officer using a computer. However, in this case the computerized system has flaws because almost all of the diagnosis and the code has been entered are not precise. The Aim of Research : The aim of research to determine the level of accuracy of the ICD-10 diagnosis of patients using a computerized system at Pertamina Hospital in Cirebon. The Methodology of Research : The research methodology used is descriptive with qualitative approach and cross-sectional design. In this research, Samples were obtained by using the simple random sampling technique. it means the sample drawn from members of the population by using the a random method, regardless of the levels of the members of the population. And the method of data collection by using the documentation study, observation and interviews. The Results of Research :The implementation of hospitalized patients encoding at Pertamina Hospital - Cirebon performed by nurses, no one coder for coding the patient's disease. The right diagnosis code of hospiatlized patients about 35%, or as much as 70 files has right medical record. About 64% diagnosis code of hospitalized patients is not appropriate, or as much as 129 files has not appropriate medical record. And about 1% diagnosis code of hospitalized patients are not filled, or as much as 3 files medical record. Diagnosis hospitalized patients are appropriate about 43% (138 right diagnosis), Diagnosis hospitalized patients are not appropriate about 57% (182 not appropriate diagnosis). The high rates of innaccuracy diagnosis codes and unconfirmity diagnosis hospitalized patients caused by man resource factors. Doctorâs prescription writing is difficult to read, lack of knowledge about ICD-10 in nurses, and there is no one a special officer for coding (coder) are the cause of the high rate of inaccuracy hospitalized patients diagnosis codes.